Analisis Job Design dan Budaya Kerja Terhadap Kinerja Karyawan Pada Bank BTPN Cabang Bawakaraeng Makassar - Fitri Handayani; Seniorita Seniorita; Samsul Rizal; Irwan Abdullah (Perkumpulan Dosen Muslim Indonesia, 2022)
This study aims to determine: (1) the effect of job design on employee performance, (2) the influence of work culture on employee performance. This research method used is quantitative, this research is a study that collects data or information and states variabels that describe job design and work culture on employee performance. Woth a total sample of 80 responden taken from the entire population. The instrument used in this study was a questionnaire sheet. Management is carried out by means of the SPSS program comparison t test. The results of this study use several tests, one of which is the t test using the t test, one of which is the t test using the t test, with the t test it is known that the value of t count > t table, this indicates that the hypothesis is accepted. The conclusions of the results of this study indicate that: (1) there is a significant positive effect between job design on employee from the result of the test, there is it count 0.5480 > t table 1.990 (2) there is no significant positive influence between work culture on performance at the Bawakaraeng Branch Bank From the test result t count -1.787 < t table 1.990.